Ответ:
Пошаговое объяснение:
1. 3^5 * 3^(-2) * 3^(-3) = 3^(5 + (-2) + (-3)) = 3^0 = 1
Ответ : 1) 1
2. a^( ( (5 + (-2) )*6) - 4) = a^14
Ответ : 1) a^14
3. 3x^2 * (2x)^3 * 1 / 3 * x^(-1) = x^2 * 8x^3 * x^(-1) = 8x^(2+ 3 + (-1)) = 8x^4
x = -1 / 2
8 * (-1 / 2)^4 = 8 * 1 / 16 = 1 / 2 = 0,5
Ответ : 3) 0,5
4. ![\frac{x^2y^3}{y^-2} * \frac{x^ -3}{y^4} = x^-1 * y = \frac{y}{x} \frac{x^2y^3}{y^-2} * \frac{x^ -3}{y^4} = x^-1 * y = \frac{y}{x}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2y%5E3%7D%7By%5E-2%7D%20%2A%20%5Cfrac%7Bx%5E%20-3%7D%7By%5E4%7D%20%3D%20x%5E-1%20%20%2A%20y%20%3D%20%5Cfrac%7By%7D%7Bx%7D)
Ответ : 2) y / x
5. (22,1 * 10^6) / (10,9 * 10^3) = 2,028 * 10^3 = 2028
Ответ : 4) 2028
6. ![X = - \frac{b^3 c^2}{2a^-1} * \frac{b^2}{5a^3 c^4} = - \frac{b^5}{10a^2 c^2} X = - \frac{b^3 c^2}{2a^-1} * \frac{b^2}{5a^3 c^4} = - \frac{b^5}{10a^2 c^2}](https://tex.z-dn.net/?f=X%20%3D%20-%20%5Cfrac%7Bb%5E3%20c%5E2%7D%7B2a%5E-1%7D%20%2A%20%20%5Cfrac%7Bb%5E2%7D%7B5a%5E3%20c%5E4%7D%20%3D%20-%20%5Cfrac%7Bb%5E5%7D%7B10a%5E2%20c%5E2%7D)
Ответ : 1) - b^5 / (10a^2 * c^2)
7. 1 / 9 ; 1 / 9 ; 1 / 8 ; -8
1 / 8 - наибольшее
Ответ : 3) (1 / 2)^3
8. А) 2^3 * a^(-1 * 3) * b^(2 * 3) = 8a^(-3) * b^6 = 8b^6 / a^3 - 3)
Б) 2a^(2 * 2 - 1) * b^(4 * 2 -3) = 2a^3 * b^5 - 1)
В) 2a^2 / b^2 * b / (a^3 * b^(-3)) = 2 * a^(2 - 3) * b^(-2 + 1 - (-3)) = 2 * a^(-1) * b^2 = 2b^2 / a - 4)